ANALISA KECEPATAN FLUTTER PADA ROTOR BLADE HELIKOPTER - Adhi Kurniawan; Ismoyo Haryanto (JURNAL TEKNIK MESIN, 2013)
Flutter is dynamic aeroelastic instability characterized by sustained oscillation of structure arising from interaction between the elastic, inertial and aerodynamic forces that can acting on the rotor blade. This paper develops the equations of motion for the structural and aerodynamic forces and moments of a rotor blade Sikorsky’s UH-60 to find the flutter for several c.g position and rotor speed. The rotor blade is modeled as a uniform beam, taking the average characteristics of a real blade between 20% and 90% of its length. Natural frequencies and mode shapes are calculated using Holzer and Myklestad-Prohl method. Lagrange’s equation is applied using normal modes to find the flutter frequency and speed. Theodorsen coefficients are calculated over a range of forward velocities (input as reduced frequencies) for a specified number of elements along the blade model. P-K method is used to solve flutter equation of motion. Incorporating these coefficients into the equations of motion, a square matrix is generated from which complex eigenvalues can be derived. These eigenvalues provide the aeroelastic natural frequencies and damping coefficients for each coupled mode. The resulting flutter speed can then be determined.